WINE INTOLERANCE IN ITALY: A PILOT STUDY - CERUTTI, F.; CRESCIO, M.I.; COSTANTINI, A.; ACUTIS, P.L.; VADUANO, E.; PELETTO, S. (Italian Journal of Food Science, 2020)
Intolerance to wine has been investigated under different aspects. In our study, we explored intolerance/allergy reactions in Italy by means of a survey including 901 questionnaires. Prevalence of wine or beer intolerance was 6%, of which 11 reported that was verified by a doctor. Odds ratio for wine intolerance with another declared allergy/intolerance is 1.6. In conclusion, we observed a high prevalence of intolerance to wine in Italy, highlighting that some sections of the population (young people and women) may be more exposed to these phenomena.